Cause, 1861 : DVD Spcial Features - Ken Burns (Hollywood, CA PBS Home Video, 1990)
Hailed as a film masterpiece and landmark in historical storytelling, Ken Burn's epic documentary brings to life America's most destructive--and defining--conflict.
Keywords: Civil War--documentary.; Episode One